Tubakia spp., Didymella macrostoma and Apiognomonia errabunda causing leaf spot and anthracnose of Quercus robur in the Mura-Drava-Danube Biosphere Reserve - Zlatković, Milica; Sallmannshofer, Markus; Schueler, Silvio; Cech, Thomas L.; Djilas, Milutin; Hoch, Gernot; Lapin, Katharina; Ogris, Nikica; Piškur, Barbara; Schwanda, Katharina; Stojnić, Srđan; Westergren, Marjana; et al. (Frontiers in Forests and Global Change, 2024)
The Mura-Drava-Danube transboundary UNESCO Biosphere Reserve represents one of the bestpreserved wetlands in Europe. The Reserve's riparian forests play a significant role in ecosystem functioning and pedunculate oak (Quercus robur) is one of the keystone species of these forests. In recent years, pedunculate oak trees in the Reserve displayed symptoms of necrotic lesions on their leaves. The lesions varied in size, from small, circular to irregular reddish brown to grayish spots to larger necrotic areas that resembled leaf anthracnose and extended along the leaf nerves. In 2021, symptomatic leaves were collected in three countries of the Reserve, i.e. Austria, Slovenia, and Serbia to identify the causative agents of these diseases. Fungal cultures were obtained from symptoms and identified using morphology and multilocus phylogenetic analyses of the ITS rDNA, partial LSU rDNA, tef 1-α, BT2, CAL, ACT, and RPB2 genes. The fungi were identified as Tubakia dryina, Tubakia sp. (Tubakia dryinoides sensu lato), Didymella macrostoma, and Apiognomonia errabunda. Pathogenicity tests done by inoculating the leaves of one-year old pedunculate oak plants revealed that the isolated fungi caused symptoms as those seen in the forest. To our knowledge, this study represents the first report of D. macrostoma as the cause of pedunculate oak leaf spot disease in Serbia and worldwide. It is also the first finding of Tubakia leaf spot disease of pedunculate oak caused by T. dryina in Austria and Serbia. Moreover, Tubakia sp. was proven to be another causative agent of Tubakia leaf spot disease. Additionally, oak anthracnose caused by A. errabunda was found for the first time on pedunculate oak leaves in Austria and Slovenia. During the past decade, pedunculate oak trees have been facing increasing threats from multiple abiotic and biotic factors which has resulted in decline and absence of natural regeneration of these trees. The results of this study add to the understanding of the contributing factors to the decline of pedunculate oak in riparian forests and are important for the development of management strategies to counteract this decline.